Moving “Forward” in Plasmodium Genetics through a Transposon-Based Approach - Bharath Balu (Journal of Tropical Medicine)
The genome sequence of the human malaria parasite, Plasmodium falciparum, was released almost a decade ago. A majority of the Plasmodium genome, however, remains annotated to code for hypothetical proteins with unknown functions. The introduction of forward genetics has provided novel means to gain a better understanding of gene functions and their associated phenotypes in Plasmodium. Even with certain limitations, the technique has already shown significant promise to increase our understanding of parasite biology needed for rationalized drug and vaccine design. Further improvements to the mutagenesis technique and the design of novel genetic screens should lead us to some exciting discoveries about the critical weaknesses of Plasmodium, and greatly aid in the development of new disease intervention strategies.